J. QUETGLAS - Breviario de Ronchamp - Pierini, Orsina Simona (ZARCH, 2018)
Josep Quetglas Breviario de Ronchamp Ediciones Asimétricas, Madrid, 2017, 275 pp., 243 ilustraciones Idioma: español. ISBN 978-84-946957-9-7